Nobiletin Regulates Polyinosinic-polycytidylic Acid-induced Inflammation in Macrophages Partially via the PPAR-γ Signaling Pathway - Yue, Ying-Xing; Huang, Shan-Shan; Weng, Ying-Zheng; Lu, Yan; Jia, Bing-Bing; Yang, Zhou-Xin (Current Pharmaceutical Design, 2024)
Introduction Macrophage dysregulation is a common pathogenic feature of viruses that provides extensive targets for antiviral therapy. Nobiletin, a polymethoxylated flavonoid found in citrus fruits, has a multitude of effects. Methods We investigated the effect of nobiletin on polyinosinic-polycytidylic acid (poly(I:C))-induced inflammation in RAW264.7 cells. Results Nobiletin inhibited the production of poly(I:C)-induced inflammatory factors, including tumor necrosis factor (TNF)-α, interleukin (IL)-6, and CXCL10. High-throughput sequencing revealed that nobiletin inhibited the expression of TNF-α, IL-6, and CXCL10 and promoted the expression of CD206, Chil3, and Vcam1. In the Kyoto Encyclopedia of Genes and Genomes enrichment analyses, the upregulated differential genes were significantly enriched in the peroxisome proliferator-activated receptor (PPAR) signaling pathway. The PPAR-γ inhibitor T0070907 significantly reversed the inhibitory effects of nobiletin on IL-6 and CXCL10 but had no significant effect on TNF-α secretion. Conclusion Thus, nobiletin regulated poly(I:C)-induced inflammatory responses in RAW264.7 cells partially via the PPAR-γ signaling pathway.
Keywords: macrophages